Effectiveness of pocketbook as the media of preconception nutrition education - Pasaribu, Rina Doriana; Aritonang, Evawani Yunita; Zuska, Fikarwin; Sudaryati, Etti (Intelektual Pustaka Media Utama, 2024)
Nutrition improvement in preconception women is a new paradigm in dealing with nutritional problems. Preconception nutrition intervention is a strategic way to break the phenomenon of stunting between generations. This study aimed to compare the effectiveness of nutrition education through pocketbooks and lectures on knowledge and attitudes. This study was used as a quasi-experiment with a pretest-posttest control group design. The population in this study were all pharmaceutical students and health analysts at Politeknik Kesehatan Medan. The minimum sample is using Hypothesis tests for two proportions (n=100). Sample selection used a simple random sampling technique. The intervention group was given a pocketbook and the control group was given a lecture. Respondents’ knowledge and attitudes were measured before and after treatment using a questionnaire. Data were analyzed by paired t-test and independent t-test. Nutrition education through pocketbooks and lectures had a significant effect on knowledge and attitudes about preconception nutrition (p<0.001), but the pocketbook was more effective than the lecture method in increasing knowledge (p<0.001) and attitudes (p=0.017). Preconception nutrition education by providing pocketbooks is effectively used as a preconception nutrition intervention with a wider target range, and time efficiency, and does not depend on material providers.